O erudito e o popular em as Intermitências da morte, José Saramago - Amorim, José do Carmo (2013)
This dissertation presents as its principal objective an analysis of the work As intermitências da morte, by the Portuguese author José Saramago. There are few studies about this theme and, therefore, in the intention of adding bibliography to the studies about death on Saramago, we decided to increase the debate about that subject. This dissertation search to read and interpret this novel by the view of the circularity between erudite and popular cultures. Our studies are based both on Câmara Cascudo s studies, with his tales of the Portuguese- Brazilian folklore, and on the analysis made by Carlo Ginzburg and Bakhtin, about the intertextual dialogue between academy and folk. About the questions that concerns the myth, our studies are supported by Eliade, the Bible and the anthropological and philosophical studies about the death and the institutions that drill it, such as the Church, the government, the politics. This work also search to analyze the structure and the composition of the novel As intermitências da morte, by José Saramago. Our view touches the folkloric tales and myths that treat the theme of death and also touches works considered erudite in the academic sphere, such as The Picture of Dorian Gray, Dante s Divine Comedy, among others.